KERUKUNAN ANTARA MASYARAKAT DENGAN ALIRAN YANG BERBEDA DI DAERAH LOMBANG-LOMBANG, KELURAHAN SINYONYOI - Abdi Akbar Al-Faridzy; Munawir Ihsan; Nurul Hidayah; Anugrah Indah Cahyani (IAI DDI Mangkoso, 2023)
Indonesia is a country characterized by a high level of social and religious diversity, including diversity of religious streams within the same religion. Differences in religious streams have the potential to generate social conflict if they are not properly managed; however, they can also foster harmonious social relations when addressed with tolerance and mutual respect. This study aims to examine the forms of harmony among communities with different religious streams and to identify the factors that support the maintenance of social harmony in Lombang-Lombang, Sinyonyoi Village. This study employs a qualitative approach with a field research design. Data were collected through observation, in-depth interviews, and documentation. Informants were selected using purposive sampling and included religious leaders, heads of Islamic study groups (majelis taklim), community leaders, and village government officials. The collected data were analyzed using descriptive qualitative methods through data reduction, data presentation, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings indicate that harmony among communities with different religious streams in Lombang-Lombang is constructed through continuous social interaction and a collective awareness of the importance of peaceful coexistence. Harmony is manifested in mutual respect, tolerance in religious practices, and cooperation in various social and community activities. The preservation of this harmony is supported by the roles of religious leaders who emphasize moral values and brotherhood, majelis taklim that instill tolerant attitudes, a village government that maintains neutrality and inclusivity, and community leaders who strengthen social cohesion through exemplary conduct and shared experiences. This study concludes that social harmony amid religious diversity is the result of synergy among religious, social, and structural factors that must be continuously maintained.